COVID-19 and gynecological cancer: a review of the published guidelines. Issue 9 (23rd June 2020) - Uwins, Christina; Bhandoria, Geetu Prakash; Shylasree, TS; Butler-Manuel, Simon; Ellis, Patricia; Chatterjee, Jayanta; Tailor, Anil; Stewart, Alexandra; Michael, Agnieszka
Abstract : On March 11, 2020 the COVID-19 outbreak was declared a 'pandemic' by the World Health Organization. COVID-19 is associated with higher surgical morbidity and mortality. An array of guidelines on the management of cancer during this pandemic have been published since the first reports of the outbreak. This narrative review brings all the relevant information from the guidelines together into one document, to support patient care. We present a detailed review of published guidelines, statements, comments from peer-reviewed journals, and nationally/internationally recognized professional bodies and societies' web pages (in English or with English translation available) between December 1, 2019 and May 27, 2020. Search terms included combinations of COVID, SARS-COV-2, guideline, gynecology, oncology, gynecological, cancer. Recommendations for surgical and oncological prioritization of gynecological cancers are discussed and summarized. The role of minimally invasive surgery, patient perspectives, medico-legal aspects, and clinical trials during the pandemic are also discussed. The consensus is that elective benign surgery should cease and cancer surgery, chemotherapy, and radiotherapy should continue based on prioritization. Patient and staff face-to-face interactions should be limited, and health resources used efficiently using prioritization strategies. This review and the guidelines on which it is based support the difficult decisions currently facing us in gynecological cancer. It is a balancing act: limited resources and a hostile environment pitted against the time-sensitive nature of cancer treatment. We can only hope to do our best for our patients with the resources available to us.